2017
DOI: 10.1002/erv.2554
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Face and Body Motion in Bulimia Nervosa

Abstract: Social cognition has been studied extensively in anorexia nervosa (AN), but there are few studies in bulimia nervosa (BN). This study investigated the ability of people with BN to recognise emotions in ambiguous facial expressions and in body movement. Participants were 26 women with BN, who were compared with 35 with AN, and 42 healthy controls. Participants completed an emotion recognition task by using faces portraying blended emotions, along with a body emotion recognition task by using videos of point-lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Two main conclusions may be drawn from the current review. First, the social cognitive problems found in most of the psychiatric samples using PLDs were of smaller magnitude than that found for other methods of social stimuli presentation (e.g., face, voice; SCZ: Okruszek and Pilecka, 2017 ; BD: Vaskinn et al, 2017 ; AN/BN: Dapelo et al, 2017 ; BPD: Kaletsch et al, 2014a ). It has been suggested that the contribution of body motion to processing information about a person may be particularly important when viewing conditions are suboptimal or the person is viewed at a distance (Yovel and O’Toole, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Two main conclusions may be drawn from the current review. First, the social cognitive problems found in most of the psychiatric samples using PLDs were of smaller magnitude than that found for other methods of social stimuli presentation (e.g., face, voice; SCZ: Okruszek and Pilecka, 2017 ; BD: Vaskinn et al, 2017 ; AN/BN: Dapelo et al, 2017 ; BPD: Kaletsch et al, 2014a ). It has been suggested that the contribution of body motion to processing information about a person may be particularly important when viewing conditions are suboptimal or the person is viewed at a distance (Yovel and O’Toole, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…Most of the studies which examined processing of emotion from PLDs in psychiatric populations (Schizophrenia: Bigelow et al, 2006 ; Couture et al, 2010 ; Henry et al, 2010 ; Brittain et al, 2012 ; Kern et al, 2013 ; Vaskinn et al, 2016 ; Bipolar Disorder: Vaskinn et al, 2017 ; MDD: Loi et al, 2013 ; Eating Disorders: Zucker et al, 2013 ; Lang et al, 2015 ; Dapelo et al, 2017 ; Alzheimer’s Dementia: Henry et al, 2012 ) utilized stimuli developed by Heberlein et al ( 2004 ). During the Emotion from the Biological Motion task (EBM) participant observes a single point-light agent walking across the screen and his/her task is to select the alternative which best describes agent’s affective state (happiness, sadness, fear, anger, neutral).…”
Section: Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Some aspects of BM processing are atypical in ASD (e.g., Klin et al, 2009;Nackaerts et al, 2012;Jack et al, 2017), schizophrenia (e.g., Kim et al, 2011;Hastings et al, 2013;Spencer et al, 2013;Hashimoto et al, 2014;Vaskinn et al, 2016Vaskinn et al, , 2018Engelstad et al, 2017Engelstad et al, , 2018aOkruszek et al, 2018) and schizotypal personality disorder (Hur et al, 2016), bipolar disorders , attention deficit hyperactivity disorder (ADHD) (Kröger et al, 2014), anxiety disorders and in individuals with elevated anxiety (van de Cruys et al, 2013;Heenan and Troje, 2015), obsessive compulsive disorders (Kim et al, 2008), and unipolar depression (Loi et al, 2013;Kaletsch et al, 2014). Deficits are also reported in individuals who were born preterm and suffer congenital brain lesions ), Alzheimer's (Henry et al, 2012;Insch et al, 2015) and Parkinson's diseases (Cao et al, 2015;Jaywant et al, 2016a,b;Kloeters et al, 2017), epilepsy (Bala et al, 2018), and eating disorders such as anorexia nervosa and bulimia (Zucker et al, 2013;Lang et al, 2015;Dapelo et al, 2017). Most of these disorders that are characterized by aberrant social cognition display a skewed sex ratio: females and males are affected differently in terms of clinical picture, prevalence, and severity (Pavlova, 2012(Pavlova, , 2017a.…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on women has shown consistent difficulties in executive functions, in particular in cognitive flexibility, central coherence, decision-making and inhibitory control (Bentz, Jepsen, Kjaersdam Telleus, et al, 2017;Buzzichelli et al, 2018;Giannunzio et al, 2018;Hamatani et al, 2018;Harper et al, 2017;Hirst et al, 2017;Kanakam, Krug, Collier, & Treasure, 2017;Overas, Kapstad, Brunborg, Landro, & Ro, 2017;Smith, Mason, Johnson, Lavender, & Wonderlich, 2018;Steward et al, 2016;Weinbach, Perry, Sher, Lock, & Henik, 2017;Zegarra-Valdivia & Chino-Vilca, 2018), and in social functions, mainly in theory of mind and affect recognition Bora & Kose, 2016;Brockmeyer et al, 2016;Dapelo et al, 2017;Fujiwara, Kube, Rochman, Macrae-Korobkov, & Peynenburg, 2017;Postorino et al, 2017;Zegarra-Valdivia & Chino-Vilca, 2018). In contrast, language (Overas et al, 2017;Spitoni et al, 2018) and orientation (Spitoni et al, 2018) frequently appear to be preserved.…”
Section: Introductionmentioning
confidence: 99%